2014
DOI: 10.1111/gfl.12084
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent Li isotope ratios in Appalachian Plateau and Gulf Coast Sedimentary Basin saline water

Abstract: Lithium (Li) concentrations of produced water from unconventional (horizontally drilled and hydraulically fractured shale) and conventional gas wells in Devonian reservoirs in the Appalachian Plateau region of western Pennsylvania range from 0.6 to 17 mmol kg À1 , and Li isotope ratios, expressed as in d 7 Li, range from +8.2 to +15&. Li concentrations are as high as 40 mmol kg À1 in produced waters from Plio-Pleistocene through Jurassicaged reservoirs in the Gulf Coast Sedimentary Basin analyzed for this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
(101 reference statements)
1
21
0
Order By: Relevance
“…25 Note that the Appalachian Basin PW samples reported here, which contain the highest Li/Cl ratios with the lowest δ 7 Li (9−13‰) that overlap with the Marcellus HFFF range, were collected specifically from Lower Silurian formations that apparently experienced the greatest burial temperatures of any samples in this study. Consequently, the overlap of Li/Cl and δ 7 Li in PW from Lower Silurian conventional oil and gas wells and Marcellus HFFF is similar to that observed in other studies from the Appalachian Basin 25 and infers limitation of the use of Li as a tracer. Nonetheless, Upper Devonian PW has lower Li/Cl (2.5−6.8 × 10 −4 ) and higher δ 7 Li (17−20‰) that are distinctive from the HFFF composition.…”
Section: Environmental Science and Technologymentioning
confidence: 89%
“…25 Note that the Appalachian Basin PW samples reported here, which contain the highest Li/Cl ratios with the lowest δ 7 Li (9−13‰) that overlap with the Marcellus HFFF range, were collected specifically from Lower Silurian formations that apparently experienced the greatest burial temperatures of any samples in this study. Consequently, the overlap of Li/Cl and δ 7 Li in PW from Lower Silurian conventional oil and gas wells and Marcellus HFFF is similar to that observed in other studies from the Appalachian Basin 25 and infers limitation of the use of Li as a tracer. Nonetheless, Upper Devonian PW has lower Li/Cl (2.5−6.8 × 10 −4 ) and higher δ 7 Li (17−20‰) that are distinctive from the HFFF composition.…”
Section: Environmental Science and Technologymentioning
confidence: 89%
“…In all samples, lithium was separated from the sample matrix prior to measuring isotopic ratios. The lithium separation procedure developed in this study was modified from Choi et al (2013) and previous studies (Tomascak et al, 1999;James and Palmer, 2000;Jeffcoate et al, 2004;Magna et al, 2004;Millot et al, 2004;Macpherson et al, 2014), in order to completely separate lithium from the matrix of limestone, shale, and saline water. Choi et al (2013) reported a simple method that effectively separated lithium isotopes in variety of geological samples by only one column separation.…”
Section: Lithium Isotopesmentioning
confidence: 99%
“…Evaporation of sea water can explain the high TDS (Haluszczak et al, 2013;Rowan et al, 2015) but does not adequately explain the elevated Li concentrations in the Marcellus produced water (Macpherson et al, 2014). Diagenetic reactions with Li-bearing minerals in the shale could possibly account for anomalously high Li in Marcellus formation water (Macpherson et al, 2014). This study further investigates sources of Li by characterizing Li concentration and isotopic composition in both formation waters and rock samples of the Marcellus Shale.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chemical analyses of saline water produced from oil and gas wells in the study area were compiled from the literature (Breen et al, 1985;Lowry et al, 1988;Dresel and Rose, 2010;Macpherson et al, 2014). Some data sets were incomplete.…”
Section: Methodsmentioning
confidence: 99%